Board Game Introduction of Jukung Palembang Boats for Adolescents Aged 17-25 Years in the City of Palembang - Patriansah, Mukhsin; Baihaqi, Muhammad Ariq (V-art: Journal of Fine Art, 2024)
South Sumatra with its capital city Palembang, is part of the island of Sumatra which has an area of 91,806.36 km2. because it is fed by many rivers, the mobility and needs of the people in the South Sumatra Province are basically very dependent on the main rivers, namely the Musi River and its tributaries. Many traditional ships pass through the Musi River, one of which is the Jukung ship which is usually one of the transportation used by the community to travel from one region to another and is also used to transport staples or trade goods and agricultural products. The design of the introduction of the Jukung ship is one of the preservation efforts to increase understanding in adolescents and the community. In overcoming these problems, the author uses the design thinking method for data collection and data analysis through the 5W+1H method (what, why, who, where, why, how), so as to produce an idea that can be applied at the design stage. The designed works are categorized into three media, namely issue media including, posters, x-banners, main media in the form of board games, and supporting media including, t-shirts, miniature Jukung ships, totebags, stickers, puzzles, pencil pouches, key chains. The application of the media uses illustrations of Jukung ships, rivers, ampera and other supporting elements, it is hoped that this design can embrace teenagers.